PERIODICAL PRESS OF SURKHONDARYA REGION IN THE YEARS OF INDEPENDENCE (TAMADDUN NURI JURNALI, 2025)
After Uzbekistan gained independence, the media, in particular the press, played a crucial role in informing the population about the changes in the life of the country and the reforms being implemented. In Surkhandarya region, each district also had its own newspaper. These publications regularly reported on socio-political and spiritual changes.